2007
DOI: 10.1128/jcm.01454-06
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of the pncA Gene in Members of the Mycobacterium tuberculosis Complex Has Important Diagnostic Applications: Identification of a Species-Specific pncA Mutation in “ Mycobacterium canettii ” and the Reliable and Rapid Predictor of Pyrazinamide Resistance

Abstract: Testing for susceptibility to pyrazinamide (PZA) and analysis of the pncA gene sequences of 423 Mycobacterium tuberculosis complex isolates have revealed a unique silent nucleotide substitution that enables the rapid identification of "M. canettii" (proposed name). Moreover, the lack of a defined mutation within the pncA gene strongly suggests that an alternative mechanism is responsible for PZA resistance. Our results indicate that DNA sequencing of the pncA gene has the potential to shorten the turnaround ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 27 publications
(27 reference statements)
3
53
0
Order By: Relevance
“…Results of these assays revealed that the isolate carried the "Mycobacterium canettii"-specific C-to-T mutation in the hsp65 gene (8) and the A-to-G mutation at position 138 in the pncA gene (22). Deletion analysis identified the presence of RD1, RD4, RD9, RD10, and tuberculosis-specific deletion 1 as well as the absence of RD12, also characteristic for "M. canettii" (10).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of these assays revealed that the isolate carried the "Mycobacterium canettii"-specific C-to-T mutation in the hsp65 gene (8) and the A-to-G mutation at position 138 in the pncA gene (22). Deletion analysis identified the presence of RD1, RD4, RD9, RD10, and tuberculosis-specific deletion 1 as well as the absence of RD12, also characteristic for "M. canettii" (10).…”
Section: Case Reportmentioning
confidence: 99%
“…Genetic analysis of the isolate was performed according to the following technologies: PCR-restriction fragment length polymorphism analysis of the hsp65 gene, mutation analysis of the pncA gene by automated DNA sequencing, PCR-based genomic deletion analysis (region of difference 1 [RD1], RD4, RD9, RD10, RD12, and M. tuberculosis-specific deletion 1), and spoligotyping (8,16,17,21,22). Results of these assays revealed that the isolate carried the "Mycobacterium canettii"-specific C-to-T mutation in the hsp65 gene (8) and the A-to-G mutation at position 138 in the pncA gene (22).…”
Section: Case Reportmentioning
confidence: 99%
“…The complex of Mycobacterium tuberculosis (MTB), including M. tuberculosis, M. africanum, M. bovis, Bovis BCG, M. caprae, M. microti, M. pinnipedii, M. dassie bacillus and M. canettii, although shows different phenotype characteristics in their biochemical tests, but they have high similarity in genetic terms [4]. To differentiate complex members is essential to promote successful treatment, especially in areas where the disease is epidemic or exposure to human and animal is high [5].…”
Section: Introductionmentioning
confidence: 99%
“…The mtp-40 and CYP 141 genes are not present in all members of the Mycobacterium tuberculosis strains and, therefore, are not useful for differentiating Mycobacterium tuberculosis from Mycobacterium bovis (10,11). The gene for histone-like protein hupB of Mycobacterium tuberculosis has been identified as a target for differentiation of MTB complex and also polymorphisms in pncA and oxyR are good options for rapidly differentiate M. bovis from M. tuberculosis; thus, for rapid and reliable detection of Mycobacterium tuberculosis complex from clinical specimens, it is needed to study genes that are simply analyzed and are conserved (9)(10)(11)(12).…”
mentioning
confidence: 99%